Analisis Faktor Risiko Penyebab Kejadian Hipertensi di Wilayah Kerja UPTD Puskesmas Sukmajaya Kota Depok Tahun 2022: Analysis of Risk Factors Causing Hypertension in the Working Area of ​​the UPTD Sukmajaya Health Center, Depok City in 2022 - Yana Efendi; Nina Nina; Assandra Cahya Arum; Dewi Ulina; Fairuz Luthfan Zaki; Maulidya Putri Mustafa; Riza Maryani (MPI Press, 2023)
Introduction: Hypertension is a public health problem that needs attention because the incidence is quite high in Indonesian society. Objectives: This study aims to determine the risk factors that cause hypertension in the working area of UPTD Puskesmas Sukmajaya Depok City in 2022. Method: This study used a descriptive quantitative research design. The population in this study was 68 patients at the Sukmajaya Public Health Center, Depok. The collection in this study was carried out offline, through questionnaire observations the data were processed and analyzed using Microsoft excel. Data analysis included univariate analysis by looking for frequency distributions. Result: The results showed that from 68 respondents, from the aspect of characteristics 43 (63%) women experienced hypertension. Then from the behavioral aspect of respondents who smoke regularly as many as 10 people (14.7), respondents who always do regular health checks 12 people (17.6%). Conclusion: This study concludes that factors that influence the incidence of hypertension are genetic factors, characteristics and behavior of the community in the working area of UPTD Puskesmas Sukmajaya Depok City in 2022.